Assessing the public attitude toward low-income housing; (case study: Small- and medium-density cities of Iran) - Ramzanpour, Mehrnaz; Sharghi, Ali; Nourtaghani, Abdolmajid (Frontiers in Built Environment, 2022)
Low-income housing (LIH) is subject to stigma. This study aims to measure public attitude toward it with respect to three main attitude components. The survey was carried out by online questionnaire and non-residents sample. Using exploratory factor analysis, 11 factors were derived including 7 cognitive factors (Security, unit characteristic, spatial reputation, individual and environmental characteristics, physical attractiveness, and social interaction), 2 affective factors (feeling toward physical dimension and feeling toward the residents), and 2 behavioral factors (social distance and situational behavior). Descriptive analysis may show that the attitude toward LIH is lower than the average level in Iran. Among them, physical factors related to environment and building possess the lowest scores of means. Thus, it is necessary to pay more attention to the reduction of stigma in LIHs and interventions in the physical aspect. The regression test showed the highest correlation among the “social distance” and “feeling toward physical aspects”; whereas the highest correlation was observed among “situational behavior” and feeling “toward residents”.